2004
DOI: 10.1007/s00421-004-1157-7
|View full text |Cite
|
Sign up to set email alerts
|

Postural control in athletes participating in an ironman triathlon

Abstract: We studied the degree of dependence on vision of static postural control among ten male adult ironmen and ten healthy subjects (firemen, control group) who took part in regular physical activity, and the perturbations of equilibrium after prolonged exercise in ironmen. Static postural stability was measured during standing on a single-force platform alternating between eyes open and eyes closed. First, body sway was analysed on a force plate in both groups, and the athletes then took part in an ironman triathl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
90
3
9

Year Published

2007
2007
2020
2020

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 108 publications
(107 citation statements)
references
References 39 publications
2
90
3
9
Order By: Relevance
“…It has been previously described that exercise at the RCP increases postural instability (Guidetti et al, 2011). However, that study was conducted on a treadmill which can influence visual, vestibular and somatic sensors affecting the postural control (Nagy, Toth, Janositz, Kovacs, Feher-Kiss, & Angyan, 2004). Our study contradicts the data by which reported higher values of LT4 (exercise intensity at which blood lactate concentration reaches a concentration of 4 mmol.L -1 ) and an inverse correlation between the LT4 and ranking position.…”
Section: Discussioncontrasting
confidence: 99%
“…It has been previously described that exercise at the RCP increases postural instability (Guidetti et al, 2011). However, that study was conducted on a treadmill which can influence visual, vestibular and somatic sensors affecting the postural control (Nagy, Toth, Janositz, Kovacs, Feher-Kiss, & Angyan, 2004). Our study contradicts the data by which reported higher values of LT4 (exercise intensity at which blood lactate concentration reaches a concentration of 4 mmol.L -1 ) and an inverse correlation between the LT4 and ranking position.…”
Section: Discussioncontrasting
confidence: 99%
“…14,19 A few authors 20,21 have evaluated the fatiguing effects of actual sport performance in triathletes 22 and soccer players. In particular, Zemkova and Hamar 20 and Brito et al 21 analyzed center-of-pressure (COP) velocity of 19-to 21-year-old players (unipedal and bipedal stances with eyes open or closed) before a game, in the break period between the first and second halves, and after a game.…”
Section: Balance and Fatiguementioning
confidence: 99%
“…Subsequently, a decrease was shown (17) in lower limb-tracking performance immediately after exercising to 50% exhaustion, i.e., short-term metabolic fatigue. However, this type of error can largely be compensated for visually (27,43), and there is indeed a proportionate enhancement of central motor effort during short-term (18) and long-term (6) fatigue. In addition, there is a slower reaction time to auditory stimulus during postexercise balance control (42), suggesting an additional attentional demand during fatigue.…”
mentioning
confidence: 99%